«Sono andato perduto al mondo»: Estetica, esperienza, mondo, sofferenza in Franz Kafka (Balthazar, 2024)
The different conceptions of apperception elaborated by Brod and Kafka are compared by pointing out that Brod focuses on the intellectual or conceptual interpretation of the concept and Kafka on the aesthetical one since it seems to be the major difference between the two. This also involves the modern conception of the new and the traditional one of the differences between form and content. Relating Kafka’s notes on aesthetics to his first and contemporary tale, Description of a Battle, it becomes clear that there is no self-consciousness, identity, liberty, or experience of the world. Apperception, for Kafka, is an aesthetic movement, and the new depends on the relationship between the artwork and its fruition. This makes the new of an artwork the consequence of a dynamic relationship linked to imagination and reflection more than of rational thought. This also means that totality in a work of art is necessary but impossible to obtain. For Kafka the difference between self-consciousness and the world has been eliminated. Thus, the new becomes the return of the same; in the modern world, the chock and the chock is perception. This is also the moment of redemption in Kafka’s writings, the moment in which the content musically transcends the form. It’s a total suspension of time, the redemption, and it appears in Kafka only in the form of a gesture, which has been lost by the world. A gesture, a name, the totality of experience, the redemption – this may be possible only by acting in a way that forces the angels to work.
Keywords: Literature; Aesthetic Apperception; Realism; Alienation; Experience; Chock; Imagination; Gesture; Intermundia; Music; History; Redemption